Studi Literatur Keanekaragaman dan Fungsi Flora di Hutan Tropis Pegunungan Sulawesi: A Literature Review on the Diversity and Ecological Functions of Flora in the Montane Tropical Forests of Sulawesi - Priyono, Aulya Aginia; nurfatimah, Destia bisma; umaroh, jelinda; nuraeni, Eni (Fakultas Kehutanan Universitas Jambi, 2026)
ABSTRACT Central Sulawesi, situated at the heart of Wallacea, supports unique tropical forest flora resulting from a complex geological history, steep elevational gradients, and ultramafic soils. This literature review aims to synthesize current knowledge on the diversity, vegetation structure, and ecological functions of flora in Central Sulawesi’s forests, focusing on Lore Lindu National Park, Mount Ambang, and Mount Lokon. A narrative synthesis was conducted using 10 peer-reviewed articles (2013–2025) from academic databases including Google Scholar, SINTA, and ScienceDirect. Results indicate a clear vertical zonation: lowland forests are species-rich with dense canopies, while montane zones (800–2,600 m asl) are dominated by Fagaceae, Myrtaceae, and Podocarpaceae, often with high endemism. Flora in ultramafic areas exhibit specialized adaptations due to edaphic stress. Ecologically, these forests stabilize slopes, enhance water infiltration, and store significant carbon. However, anthropogenic pressures especially nickel mining and habitat fragmentation severely threaten ecosystem integrity and increase extinction risks for endemic species. This study underscores the need for landscape-scale conservation that integrates habitat protection, restoration, and community engagement to sustain both biodiversity and ecosystem services in Central Sulawesi. Keywords: deforestation, endemic flora, montane forest, Central Sulawesi, Wallacea ABSTRAK Sulawesi Tengah terletak di jantung Wallacea dan memiliki flora hutan tropis yang unik akibat sejarah geologis yang kompleks, gradien elevasi yang tajam, serta tanah ultramafik.Studi ini bertujuan mengkaji keanekaragaman, struktur vegetasi, dan fungsi ekologis flora di hutan Sulawesi Tengah, khususnya di Taman Nasional Lore Lindu, Gunung Ambang, dan Gunung Lokon. Metode yang digunakan adalah sintesis naratif berdasarkan 10 artikel ilmiah (2013–2025) dari Google Scholar, SINTA, dan ScienceDirect. Hasil menunjukkan adanya zonasi vertikal: hutan dataran rendah kaya spesies dengan kanopi rapat, sedangkan hutan montane (800–2.600 m dpl) didominasi Fagaceae, Myrtaceae, dan Podocarpaceae dengan tingkat endemisme tinggi. Tumbuhan di tanah ultramafik menunjukkan adaptasi khusus. Secara ekologis, hutan ini menstabilkan lereng, meningkatkan infiltrasi air, dan menyimpan karbon. Namun, tekanan antropogenik terutama pertambangan nikel dan fragmentasi mengancam keberlanjutan ekosistem dan meningkatkan risiko kepunahan spesies endemik. Temuan ini menegaskan perlunya strategi konservasi berbasis lanskap yang mengintegrasikan perlindungan habitat, pemulihan ekosistem, dan keterlibatan Masyarakat. Kata kunci: deforestasi, flora endemik, hutan montane, Sulawesi Tengah, Wallacea